Higher Pentraxin‐3 Levels are Associated With Inflammation in Familial Mediterranean Fever. Issue 6 (13th April 2016) - Bulut, Mesudiye; Ceri, Mevlut; Unverdi, Selman; Altay, Mustafa; Senes, Mehmet; Ecemis, Zafer Aydın; Duranay, Murat
Abstract : Background: Circulating levels of Pentraxin‐3 (PTX3) have been shown to increase in several inflammatory conditions. However, there is no information about the levels of PTX3 in patients with familial Mediterranean fever (FMF). This study was designed to evaluate the serum PTX3 levels in patients with FMF during attack and free‐attack periods. Methods: Twenty FMF patients in attack and free‐attack period, and 20 age‐, sex‐, and body mass index‐matched healthy controls were included in the study. Blood samples were obtained within the first 24 h of the attack period and between attacks, and levels of white blood cell, erythrocyte sedimentation rate, Fibrinogen, high sensitive CRP, and PTX3 were determined. Results: PTX3 levels during the attack period were not significantly different from those in free‐attack patients (4.9 ± 4.6 ng/ml vs. 2.8 ± 1.4 ng/ml, P > 0.05). However, both attack and free‐attack patients had significantly higher PTX3 levels than healthy controls (4.9 ± 4.6 ng/ml vs. 1.8 ± 0.8 ng/ml, P < 0.001; 2.8 ± 1.4 ng/ml vs. 1.8 ± 0.8 ng/ml, P < 0.025, respectively). Conclusions: PTX3 levels were not markedly affected from FMF attacks, but high level of PTX3 in free‐attack period of FMF patients shows ongoing subclinical inflammation. However, further studies are needed to determine its usefulness as a marker in clinical practice.